Mental Imagery: Is It Worth the Endeavour? - Munsakorn, Nuttanuch (Mediterranean Journal of Social Sciences, 2012)
Based on current research and theory in various fields of study, mental imagery is believed as a specific type ofmemory aid which is most widely and effectively used. Unfortunately, in EFL language class, the learner received very littletraining in dealing with mental imagery as a mnemonic device. The point this paper wants to emphasize is that knowing theadvantages of mental imagery will assist the learners to be able to apply this memory device on their own. To understand thispoint, a one-group experiment was conducted to point out some of the advantages of using mental imagery of BangkokUniversity’s students in Thailand. It is hypothesized that the subjects will have better recall after being trained to utilize mentalimagery in vocabulary learning. The results shed important light on the fact that the imagery which helps the students to enlargeand improve vocabulary knowledge independently. These results do not only show positive results, but also introduce anadditional comment that the tools learners use to learn vocabulary should fit the situation in which the learners find themselves(Nist and Simpson, 2000).